2021
DOI: 10.1007/s11764-021-01152-1
|View full text |Cite
|
Sign up to set email alerts
|

Current practice patterns and gaps in guideline-concordant breast cancer survivorship care

Abstract: Purpose Breast cancer-specific survivorship care guidelines for the more than 3.8 million survivors in the U.S. are available, but implementation in clinical practice remains challenging. We examined current practice patterns and factors associated with guideline-concordant survivorship care among oncologists. Methods A national sample of medical oncologists, recruited using two databases, participated in a survey focused on practice patterns for breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Our findings reflect the dominant model of survivorship care, in which oncology specialists continue to follow their patients for years to decades after initial treatments, with no transition of care to other providers or settings [6,22]. As previously reported [17], most oncologists in this study described being the sole clinician (62%) providing follow-up care, while others collaborated with an oncology advanced practice provider (APP) in their practice (16%). Only 10% of participants reported access to a dedicated survivorship clinician (MD or NP).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our findings reflect the dominant model of survivorship care, in which oncology specialists continue to follow their patients for years to decades after initial treatments, with no transition of care to other providers or settings [6,22]. As previously reported [17], most oncologists in this study described being the sole clinician (62%) providing follow-up care, while others collaborated with an oncology advanced practice provider (APP) in their practice (16%). Only 10% of participants reported access to a dedicated survivorship clinician (MD or NP).…”
Section: Discussionsupporting
confidence: 78%
“…This is a secondary analysis of survey data from the Medical Oncologist Survivorship Study (MOSS), conducted from October 2018 to April 2020 at the University of California, Los Angeles (UCLA) [ 17 ]. The purpose of this analysis was to examine oncologist-reported barriers and motivators to addressing physical and psychosocial long-term effects using a mixed-methods approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of medical oncologists in the United States found that only 46% provided survivorship care plans for women with breast cancer, 34% assessed for emotional distress and only 34% screened for additional cancers. Reasons listed were a lack of disease-specific training, lack of understanding of survivorship issues and that women were not routinely informed about potential late effects after treatment [36]. This study explored the medical roles, but there is also a need to consider the referral and access to the broader multi-professional team to address the wide range of problems that occur in cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…This study can inform the implementation of survivorship care pathways in other centers.However, a comprehensive approach that serves all survivorship domains is insufficiently delivered in clinical practice. 13,14 This may be related to implementation challenges such as lack of health care professional awareness and training and prioritization of survivorship, organizational barriers including the need for dedicated time slots in clinics to allow for multidisciplinary assessment and management…”
mentioning
confidence: 99%